2014
DOI: 10.1186/1471-2458-14-743
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with prolonged non-nutritive sucking habits in two cohorts of Brazilian children

Abstract: BackgroundNon-nutritive sucking habits (NNSH) are very common during childhood. However, if these habits were maintained for 36 months of age or more, they are considered to be prolonged (PNNSH) and can cause occlusal, physiological and esthetic changes. There is controversy about their prevalence and whether perinatal, social, demographic and health characteristics influence their onset and duration. So, the objectives of this study are to estimate the prevalence of PNNSH and to evaluate perinatal, early life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 30 publications
3
18
0
6
Order By: Relevance
“…In contrast, short duration of breastfeeding and bottle sucking duration were consistently associated with higher prevalence of prolonged non-nutritive sucking habits. In addition, it has been observed that eating habits and nutritive sucking at the beginning of life seem to be predictors of these habits at school-age (17) . Among the factors that contribute to early weaning are socio-cultural and economic matters, the use of artificial nipples, and non-nutritive sucking, especially the use of pacifiers, which may pose a risk for HOHs (14,18) .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, short duration of breastfeeding and bottle sucking duration were consistently associated with higher prevalence of prolonged non-nutritive sucking habits. In addition, it has been observed that eating habits and nutritive sucking at the beginning of life seem to be predictors of these habits at school-age (17) . Among the factors that contribute to early weaning are socio-cultural and economic matters, the use of artificial nipples, and non-nutritive sucking, especially the use of pacifiers, which may pose a risk for HOHs (14,18) .…”
Section: Discussionmentioning
confidence: 99%
“…A pacifier (dummy) sucking is one of the most common nonnutritive sucking habits. It is a nursing object that has an imperforated nipple, such a device used by many infants and children to provide a sense of comfort, security and pleasure (1,2,3) .…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged pacifier sucking habit may produce deleterious effects (9) ,especially if it persists beyond 3 years of age (3) , including interruption of breast-feeding, or even its cessation (4,10,11) , recurrent otitis media (7) , candidal infection and thrush (12)(13)(14) .In addition, it may act as a predisposing factor that may increase the chance of developing dental caries (9,11) as well as the development of posterior cross bite which is one of the most frequent type of malocclusion associated with its prolonged use (12)(13)(14) .…”
Section: Introductionmentioning
confidence: 99%
“…Both are considered sucking habits as they involve frequent conscious and unconscious neuromuscular activities (3,4) .…”
Section: Introductionmentioning
confidence: 99%